2011
DOI: 10.1682/jrrd.2010.10.0203
|View full text |Cite
|
Sign up to set email alerts
|

Translating measurement findings into rehabilitation practice: An example using Fugl-Meyer Assessment-Upper Extremity with patients following stroke

Abstract: Abstract-Standardized assessments are critical for advancing clinical rehabilitation, yet assessment scores often provide little information for rehabilitation treatment planning. A keyform recovery map is an innovative way for a therapist to record patient responses to standardized assessment items. The form enables a therapist to view the specific items that a patient can or cannot perform. This information can assist a therapist in tailoring treatments to a patient's individual ability level. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 28 publications
0
44
0
4
Order By: Relevance
“…Six articles 19,22,27,34,35,36 were excluded because they did not meet the inclusion criteria (Appendix B). Six RCTs 20,21,[23][24][25][26] were 38 There were no reports of dropouts in any of the 6 studies. Methodologies and key findings of the studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Six articles 19,22,27,34,35,36 were excluded because they did not meet the inclusion criteria (Appendix B). Six RCTs 20,21,[23][24][25][26] were 38 There were no reports of dropouts in any of the 6 studies. Methodologies and key findings of the studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…По мнению большинства экспертов, шкала FMA-UE является хорошо продуманным, объективным и эффек-тивным методом клинического обследования больных с инсультом [6][7][8][9][10][11]. Она считается одним из наиболее точ-ных инструментов оценки нарушений двигательных функций после инсульта и используется в качестве объ-ективного показателя их ухудшения и последующего вос-становления [12][13][14][15][16][17].…”
Section: Fma-ueunclassified
“…Шкала FMA-UE может использоваться для установления цели, плана и мониторинга прогресса лече-ния пациента. Референтные значения составляют от 0 до 20 баллов -тяжелые двигательные нарушения, от 21 до 50 -умеренные и от 51 до 66 -легкие [11].…”
Section: Fma-ueunclassified
“…Standardised measurement tools with good psychometric properties provide therapists with information that is the best available and accurate evidence on which to base these decisions (Potter, Fulk, Salem, & Sullivan, 2011). Using standardised measures increases the accuracy of the occupational therapy diagnosis and potentially allows comparison with norms for that behaviour or attribute, improves the targeting of the specific intervention strategies to the functional abilities of the client, as well as assisting with identifying the specific level for the goals being set (Velozo & Woodbury, 2011). Therapists in the survey study identified some of these reasons as reasons why they assess sensory impairments.…”
Section: Utilising Standardised Sensory Measuresmentioning
confidence: 99%
“…Therapists in the survey study identified some of these reasons as reasons why they assess sensory impairments. The low level of utilisation of standardised measures may be due to difficulties relating the results from these assessments to these key components of intervention planning and CDM (Velozo & Woodbury, 2011). This concern was expressed by therapists in the qualitative study In areas where there is limited or slow development of research evidence, Unsworth (2011) stresses that using standardised outcome measures provides data that therapists can use to evaluate the effectiveness of their specific interventions and also potentially allows sharing of data that could potentially be used in research about these interventions.…”
Section: Utilising Standardised Sensory Measuresmentioning
confidence: 99%